+0  
 
0
204
1
avatar

solve for the value of Z:4(Z-4)/6 + 3Z-(1/60=3/6

Guest Mar 14, 2017
 #1
avatar+92629 
+5

4(Z-4)/6 + 3Z-(1/6)=3/6

 

\(\frac{4(Z-4)}{6} + 3Z-\frac{1}{6}=\frac{3}{6}\\ \frac{4(Z-4)}{6} + \frac{18Z}{6}-\frac{1}{6}=\frac{3}{6}\\ \frac{4(Z-4)+18Z-1}{6} =\frac{3}{6}\\ 4(Z-4)+18Z-1=3\\ 4Z-16+18Z-1=3\\ 22Z-17=3\\ 22Z=20\\ 11Z=10\\ Z=\frac{10}{11}\)‚Äč

Melody  Mar 14, 2017

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.